Distribuição espacial da deriva e depósito em folha de cafeeiro sob diferentes taxas de aplicação - Ribeiro, Gustavo Moreira (2024)
In coffee farming, spraying is used to apply nutrients and phytosanitary products, requiring the syrup to be deposited efficiently on the target. However, during application, part of the spray is lost to the environment, making it necessary to know the performance of spraying equipment to minimize losses, ensure effective control of phytosanitary problems and promote greater environmental safety. The objective of the work was to evaluate the deposition on the sprayed leaves and the losses above the canopy, on the ground and on the leaves of streets adjacent to the area applied with a hydropneumatic sprayer, at different application rates. The JA1 and MAG2 tips were used for rates of 200 and 400 L ha-1, respectively. To evaluate deposition, a marker was added to the mixture for subsequent detection in the spectrophotometer. The assessment was carried out on four adjacent streets on each side of the sprayer. The rate, application side and street were used to adjust a linear mixed model and the means were compared using the Tukey test, with Sidak adjustment. An interpolation using ordinary kriging was performed to evaluate the spatial distribution of the variables. In general, greater deposition was observed on the left side compared to the right for all variables, when greater deposition was observed on the right side, it was due to the effect of wind direction. Losses to the soil, above the canopy and on leaves in subsequent streets occurred up to the fourth street evaluated, influenced by the application rate, wind direction and droplet size. Map interpolation allowed analyzing the spatial distribution of spray losses with variables showing strong spatial dependence. The rate of 400 L ha-1 deposited more product in the directly sprayed area, showed less drift above the canopy and in the leaf of subsequent streets, but caused greater loss to the soil on the left side.